Bipolar charge transport in organic electron donor‐acceptor systems with stable organic radicals as electron‐withdrawing moieties. (29th May 2019) - Bobet, Ares; Cuadrado, Alba; Fajarí, Lluís; Sirés, Ignasi; Brillas, Enric; Almajano, Maria Pilar; Jankauskas, Vygintas; Velasco, Dolores; Juliá, Luis
Abstract: Two very stable organic radical adducts1 and2 formed by an electron donor‐acceptor system with bipolar charge transport behavior have been investigated. Both present the same electron donor moiety, 3, 6‐bis( N ‐carbazolyl)carbazole, and are distinguished by the paramagnetic electron‐withdrawing moiety, tris(2, 3, 5, 6‐tetrachlorophenyl)methyl radical (DTM) in1 and tris(2, 4, 6‐trichlorophenyl)methyl radical (TTM) in2 . They exhibit low band gaps (difference between HOMO and LUMO orbitals), 1.54 and 1.81 eV for1 and2, respectively, absorbing in the visible rang of the electromagnetic spectrum. Both radical adducts present suitable charge transport results with the DTM derivative1 showing the best performance. Thus, 1 with higher structural congestion displays a well‐balanced ambipolar behavior and the highest hole and electron mobility values. Abstract : Two new very stable radical adducts from the TTM and DTM series have been prepared and their ambipolar electrical character has been determined; both radical adducts conduct electrons and holes. The chemical oxidation of the DTM adduct retains the magnetic character of the molecule while disappearing completely in the oxidation of the TTM adduct. Other notable difference between both radical adducts is the quenching of luminescence of the DTM adduct and the emission of luminescence of the TTM adduct in non polar solvents.